The determinants of crime rates in Malaysia / Amiera Mahmuda Mahmud - Mahmud, Amiera Mahmuda (Faculty of Business and Management, 2015)
This study was made because nowadays a lot of Malaysian likes to involve in an stock investment industry. This is because of the most of the people think that stock investment industry was one of the good ways of increasing the volume of money. This situation will make that the stock investment industry will become bigger. As we all know, investment in stock will involve with a lot of risk that each of their trader will face on. The risk in investment in stock is common to the trader. Usually the risk is came from many source of aspect either internal or external factor. Most of the researches are using an internal factor to forecast the condition of the changes in the stock market price. There are a lot of indicator that investor used as a guideline to trace the changes in stock market price. The major indicator was interest rate, exchange rate, money supply, crude oil price, consumer price index, gold price and other microeconomic factor. The purpose of the study is to find the factor that affecting the stock market price in Malaysia. This study was more focus on the microeconomic factor which is interest rate, money supply, exchange rate, consumer price index, reserve and crude oil price. This study will help to identify the factors that will affect stock market price from 1980 to 2013 in yearly basis. This study will help the investor to trace what is the accurate factor that will affect stock market price. The analysis involve in this study was using multiple regression model have shown the independent variable is significant to the stock market price. Based on the regression, there had only four significant independents variable which is interest rate, money supply, exchange rate and reserve.